Eleição de líder com qualidade de serviço para o modelo falha-e-recuperação - Reis, Vinícius Angiolucci (2017)
A distributed system is a set of processes and links that is desgined to provide computing power and data persistency, even on the presence of failures. To encapsulate the abstraction of time and to determine which processes have currently failed, these distributed systems are based on unreliable failure detectors, which in its turn are used as a leader election service. Many works are dedicated to analyze the quality of service (QoS) of failure detectors, but a few of them has analyzed the QoS of a leader election algorithm. In this work, we present the NFD-L leader election algorithm, designed to work on crash-recovery distributed systems and to follow the QoS specification defined by Chen, Toueg e Aguilera (2002). We used NFD-L to elect Paxos coordinators for a replication framework and compared the observed QoS for NFD-L with the behavior of the framework native leader election algorithm that is not designed to explicitly meet any QoS requirement.